PENGEMBANGAN E-LKPD BERDIFERENSIASI BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL KELAS X DI SMKN 1 LINGGO SARI BAGANTI - Anggun Vitaloka; Alfi Yunita; Hafizah Delyana (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research is motivated because the LKPD used as a companion to mathematics learning activities at SMKN 1 Linggo Sari Baganti is less interesting for students and has not utilized technology. The purpose of the study was to determine the validity and practicality of Problem Based Learning based differentiated E-LKPD on SPLTV class X material at SMKN 1 Linggo Sari Baganti. The type of research used is research and development (R&D) using the ADDIE development model. The stages in this study include analysis, design, development, implementation, and evaluation. The research instruments used are validation questionnaire and practicality questionnaire which are useful to see the validity and practicality of E-LKPD. Based on the validator's assessment, the validity of the Problem Based Learning-based differentiated E-LKPD was 76.97% with a valid category. The final score of the practicality of the one-on-one trial with the math teacher obtained a final score of 91.67% in the very practical category. The final score of the practicality of the one- on-one trial with students obtained a final score of 98.81% with a very practical category. The final value of the practicality of the small group trial by students was obtained at 96.83% with a very practical category. Based on the results of the study, it can be concluded that the Problem Based Learning-based differentiated E-LKPD on SPLTV material at SMKN 1 Linggo Sari Baganti is known to be valid and practical for use by teachers and students